LINGUOCULTURAL FEATURES OF PHRASEOLOGICAL UNITS - Samadova Visola Baxtiyor qizi (Western European Studies, 2025)
In this article is discussed opinions about phraseology, the origin of phraseology, phraseogical unities and phraseological fusions. It is also focused on semantic and structure of phraseological units.
Keywords: Phraseology; semantic integrity; expressiveness